Influence of light ion irradiation of the oxide layer on the oxidation rate of zircaloy-4: Irradiation of the post-transition oxide layer. (December 2019) - Tupin, Marc; Venague, Boris; Gutierrez, Gaëlle
Highlights: The emergence of two vibration bands on RAMAN spectra linked to irradiation defects. 18 O diffusion flux increase after proton irradiation. A strong kinetics acceleration after irradiation. Oxidation kinetics decrease with the irradiation defect annealing. Abstract: The corrosion behavior of Zircaloy-4 fuel cladding in nuclear reactor is affected by irradiation damage. The irradiation effect of the post-transition oxide layer on the Zircaloy-4 corrosion rate has been investigated using protons. As previously observed on pre-transition oxide layer, irradiation defects increase the oxidation rate of the alloy up to around 30 days in autoclave in agreement with the irradiation defect annealing characterized by Raman spectroscopy. The model proposed for pre-transition regime is able to describe the oxidation rate after irradiation of post-transition oxide layers.